Is there anybody out there? Insights into Teachers' Emergency Remote Teaching Experiences - Nevin Avci (Anı Publishing, 2023)
This study aims to explore the phenomenon of emergency remote teaching (ERT) during the Covid-19 pandemic in terms of teaching practices from the perspective of public high school teachers. This study, as a phenomenology design pattern in the qualitative paradigm, focused on the phenomenon of ERT as experienced by public high school teachers and as it appeared to the teachers from the first-person point of view. Data were collected from five secondary education public high school teachers who were selected through criterion and convenience sampling methods also using an individual semi-structured interview form, transcribed by dictation.io and analyzed through content analysis. This study yielded vivid descriptions through the themes of "shifting practices," "pearls and pitfalls of ERT" and "most challenging aspects of ERT experiences." Personal gains left aside, the study can provide decision-makers with insights for considering the effectiveness of the execution of ERT. The findings can be used to improve the status of ERT practices and learning at the time of crises.